The Effect of Red-Blue Led Intensity on the Growth and Yield of Lettuce Varieties Cultivated Using NFT Hydroponics - Wahyudi, Muhammad Adiyat; Atikah, Titin Apung; Syahrudin, Syahrudin; Soeparno, Soeparno; Sirenden, Ruben Tingting; Asie, Kambang Vetranie; Widyawati, Wahyu; Rahayu, Yekti Sri (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2025)
Optimizing the growth of lettuce (Lactuca sativa) under controlled lighting conditions is essential for improving indoor farming systems. Therefore, this study aims to examine the effect of the intensity of 3030 LED (light emitting diode) type 7520 red-blue Grow Light on the growth of 3 Lettuce varieties, which were cultivated using NFT hydroponics. The study procedures were carried out using Completely Randomized Design (CRD) with 2 factors. These factors included 1) intensity of the red-blue SMD 3030 LED Grow Light type 7520 with levels of 0%, 30%, 70%, and 100%, and 2) lettuce varieties, namely Batavia Caipira, Red Rapid, and New Grand Rapid. Data obtained were analyzed for variance at the 5% level and the Honest Significant Difference Test at the 5% level. The results showed that giving a red-blue SMD 3030 type 7520 LED Grow Light with an intensity of 100% to Batavia Caupa lettuce variety produced the highest number of leaves at 35, 42, and 45 days after sowing (DAS). Moreover, an intensity of 70% led to greater plant height, which was observed to be better at 45 days after sowing. LED lights with 100% intensity promoted superior growth in leaf area, fresh stover weight, and fresh root weight compared to other intensities. New Grand Rapid variety exhibited a plant height of 47 cm, a leaf area of 109.1 cm², a fresh stem weight of 144.2 g, and a dry root weight of 1.8 g, outperforming the other varieties. Meanwhile, Batavia Caipira variety produced a greater number of leaves (29.3 leaves) compared to others.